ANALYSIS OF THE EFFECT OF WORK MOTIVATION, LEADERSHIP STYLE, AND WORK FACILITIES ON EMPLOYEE PERFORMANCE AT THE TOBADAK DISTRICT OFFICE - Dewi Sartika; Herman Herman; Rohsita Amalyah Rasyid (Jurnal Ekonomi, 2023)
This study investigates the influence of work motivation, leadership style, and workplace facilities on employee performance at Kantor Kecamatan Tobadak. The research employs quantitative methods, including regression analysis, to analyze data collected through questionnaires. The results reveal significant relationships between these variables and employee performance. Work motivation positively impacts employee commitment and effort, while effective leadership fosters a collaborative work environment. Adequate workplace facilities contribute to job satisfaction and productivity. The combined effect of these factors accounts for 39% of the variation in employee performance. These findings underline the importance of a motivated workforce, positive leadership practices, and conducive facilities for enhancing employee performance. Further research could consider additional factors that might influence performance outcomes.